Spanish word orderand complement subject interpretation in control structures by adult english naitve speakers - Gonzalez, Nora (Lenguas Modernas, 2017)
The goal of the present study is to compare the acquisitional development between adult English speakers learning Spanish as a second language and children of five- to ten-years of age acquiring Spanish as a native language with respect to the syntactic structures of word order and control, The results of this study suggest some similarities and differences in the acquisition of the native (Ll) vs. The acquisition of the target language (L2). The adult English speaker follows the same acquisitional stages as the child acquiring Spanish as his/her native language. It is proposed here that these similarities are explained by assuming the innate universal language acquisition device proposed by Chomsky (1981). The differences are reflected upon the rate ofacquisition. The adult L2 learners are slower tan the children L1 learners. The adult uses the rules known in his native language in the beginning stages and then, later, he learns the rules of the target language. These differences are explained by interference of the native language.